PROSES PENGUATAN KARAKTER TANGGUNG JAWAB DENGAN METODE RESITASI PADA PEMBELAJARAN TEMATIK DI SDN 13 KOTA SERANG - Reksa Adya Pribadi; Alma Maulida; Farhan Oktavian; Salsa Novianti Ariadila (STKIP Subang, 2022)
Education is very important in human life. Because education allows humans to know their abilities and potential. In an education there are 6 characters that must be developed, one of which is the character of responsibility. Therefore, this study aims to determine the development of the character of responsibility in thematic learning using the recitation method at SDN 13 Serang City. This study uses descriptive qualitative with the subjects in this study are teachers and students of SDN 13 Serang City. Data collection techniques in this study used observation, interviews and documentation techniques. The results of this study indicate that the recitation method is considered appropriate to shape the character of student responsibility because in this method students are required to work on assignments independently and the answers will be accounted for.